Achievements and prospects of experimental pharmacology in oncology and radiation medicine. I All-Russian scientific and practical conference. A.F. Tsyba Medical Radiological Research - branch of the National Medical Research Center of Radiology of the Ministry of Health of Russia, Obninsk, March 1, 2024. - article Editorial (Сибирский онкологический журнал)
.